THE EFFECT OF REGULAR PHYSICAL ACTIVITY AND SMOKING HABIT ON BONE MASS AMONG MALE INDUSTRIAL WORKERS IN PADANG, WEST SUMATRA - Rahmi Elviana; Lusi Susanti; Hilma Raimona Zadry (Jurnal Kesehatan Masyarakat Andalas, 2019)
Labors, especially in industry, spend most of their time in the workplace. Several factors including physical activity and lifestyle of workers such as smoking habit in the workplace that will affect labors health. Besides that, bone mass is one of the factors that influence the health quality of workers, especially for hand-operated labor. This research aims to define the relationship between physical activity and smoking habit on bone mass in male industrial labors. The study is a preliminary study to recognize variables that influence bone mass and the base for defining the weight limit for lifting activities. This investigation was purposed determining physical activity and smoking habit of labors in the workplace, as well as calculating the bone mass of workers. The respondents required were 93 male labors in Padang, West Sumatra. Bone mass measuring tools were used to calculate labor's bone mass, while questionnaires were used to define the smoking habit of labors and physical activity. Physical activity, as well as smoking habit, were significantly affected the bone mass (p<0.05) of the workers. This study result explains that physical activity and smoking habit are factors that are associated with bone mass status for young male workers in Padang, West Sumatra.